Raman microspectroscopy demonstrates reduced mineralization of subchondral bone marrow lesions in knee osteoarthritis patients - Yea-Rin Lee (Bone Reports, 2020)
Introduction: Bone marrow lesions (BMLs) are frequently identified by MRI in the subchondral bone in knee osteoarthritis (KOA). BMLs are known to be closely associated with joint pain, loss of the cartilage and structural changes in the subchondral trabecular bone (SCTB). Despite this, understanding of the nature of BMLs at the trabecular tissue level is incomplete. Thus, we used Raman microspectroscopy to examine the biochemical properties of SCTB from KOA patients with presence or absence of BMLs (OA-BML, OA No-BML; respectively), in comparison with age-matched cadaveric non-symptomatic controls (Non-OA CTL). Methods: Tibial plateau (TP) specimens were collected from 19 KOA arthroplasty patients (6-Male, 13-Female; aged 56–74 years). BMLs were identified ex-vivo by MRI, using PDFS- and T1-weighted sequences. The KOA specimens were then categorized into an OA-BML group (n = 12; containing a BML within the medial condyle only) and an OA No-BML group (n = 7; with no BMLs identified in the TP). The control (CTL) group consisted of Non-OA cadaveric TP samples with no BMLs and no macroscopic or microscopic evidence of OA-related changes (n = 8; 5-Male, 3-Female; aged 44–80 years). Confocal Raman microspectroscopy, with high spatial resolution, was used to quantify the biochemical properties of SCTB tissue of both the medial and the lateral condyle in each group. Results: The ratios of peak intensity and integrated area of bone matrix mineral (Phosphate (v1), Phosphate (v2) and Phosphate (v4)), to surrogates of the organic phase of bone matrix (Amide I, Proline and Amide III), were calculated. Within the medial compartment, the mineral:organic matrix ratios were significantly lower for OA-BML, compared to Non-OA CTL. These ratios were also significantly lower for the OA-BML medial compartment, compared to the OA-BML lateral compartment. There were no group or compartmental differences for Carbonate:Phosphate (v1, v2 and v4), Amide III (α-helix):Amide III (random-coil), Hydroxyproline:Proline, or Crystallinity. Conclusion: As measured by Raman microspectroscopy, SCTB tissue in BML zones in KOA is significantly less mineralized than the corresponding zones in individuals without OA. These data are consistent with those obtained using other methods (e.g. Fourier transform infrared spectroscopy; FTIR) and with the increased rate of bone remodeling observed in BML zones. Reduced mineralization may change the biomechanical properties of the trabecular bone in BMLs and the mechanical interaction between subchondral bone and its overlying cartilage, with potential implications for the development and progression of OA.